PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT MITSUBISHI ARISTA BANDA ACEH - Farhan Syukrin; Agus Ariyanto; Husnaina Mailisa Safitri (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2026)
This study aims to analyze the effect of career development and work environment on the performance of employees at PT Mitsubishi Arista Banda Aceh. The population of this study consisted of all 44 employees, all of whom were included as the research sample. The research method used was associative with a descriptive quantitative approach based on cross-sectional data. Data were collected through observation, questionnaires, and documentation, and analyzed using SPSS version 3.0. The results showed that the career development variable (X1) had no significant effect on employee performance (Y), with a significance value of 0.144 (> 0.05). Similarly, the work environment variable (X2) also had no significant effect on employee performance (Y), with a significance value of 0.254 (> 0.05). However, simultaneously, the career development (X1) and work environment (X2) variables had a significant effect on employee performance (Y), with a significance value of 0.032 (< 0.05). These findings indicate that while individually career development and work environment do not significantly impact performance, their combination significantly contributes to improving employee performance at PT Mitsubishi Arista Banda Aceh